Belief in witch witch-killing in Dooars - Baruya, Ananya (New Delhi : Northern Book Centre, 2005)
With reference to Dooars region of India.
"University of North Bengal"--Cover.
Includes bibliographical references (p. [89]-104) and index.
Keywords: Witchcraft -- India -- Dooars; Murder -- India -- Dooars; Dooars (India) -- Religious life and customs